Screening and Assessment of Genetic Diversity of Rice (Oryza sativa L.) Germplasm in Response to Soil Salinity Stress at Germination Stage - Alia Anwar; Javaria Tabassum; Shakeel Ahmad; Muhammad Ashfaq; Adil Hussain; Muhammad Asad Ullah; Nur Shuhadah Binti Mohd Saad; Abdelhalim I. Ghazy; Muhammad Arshad Javed (Agronomy, 2025)
Salinity stress significantly affects rice yield, especially when it occurs during the germination stage. Direct seeding is an emerging method to conserve water in rice cultivation. However, to date, there have been limited efforts to screen rice germplasm for salt tolerance under this approach. In this study, 40 rice genotypes were evaluated for salt tolerance using a combination of germination and growth parameters. A total of 59 microsatellite markers were used to assess genetic diversity, revealing significant variation in both germination and growth traits. Based on germination parameters, IR36, Sri Malaysia 2, and MR185 performed well under saline conditions, while Hashemi Tarom and BAS2000 exhibited weak tolerance. MR219, MR211, and MR263 were identified as superior salt-tolerant genotypes against all growth parameters. BAS2000 and MCHKAB were identified as salt-sensitive, showing reduced growth in key traits, including root and shoot development. Marker-based genotyping identified a total of 287 alleles. The number of alleles per locus ranged from two to nine with an average of 4.86. The polymorphic information content (PIC) ranged from four to eight. The markers RM21, RM481 RM566, RM488, RM9, RM217, RM333, RM242, RM209, RM38, RM539, RM475, RM267, RM279, and RM430 were found highly polymorphic with PIC value > 0.7 and contain the highest number of alleles (≥6). Model- and distance-based population structures both inferred the presence of three clusters in the studied rice germplasm. Based on cluster analysis, Shiroodi, Hashemi Tarom, and BAS2000 were found as weak salt-tolerant varieties, whereas MR211 and MR219 are two Malaysian varieties found to be highly tolerant and have a high potential for direct seeding methods. An AMOVA test suggested that 95% genetic diversity was within the population, which implies that significant genetic variation was present in rice germplasm to be used to select parents for future breeding programs.